Role of leucyl-tRNA synthetase in regulation of branched-chain amino-acid transport. - Quay, S C (1975)
The regulation of the transport of leucine, isoleucine, and valine in Escherichia coli B/r was studied in a mutant with a complete deletion of the leucine biosynthetic operon and a temperature-sensitive leucyl-tRNA synthetase [L-leucine:tRNALeu ligase (AMP-forming), EC 6.1.1.4]. Under conditions of excess leucine and a functional leucyl-tRNA synthetase transport activity was repressed. Shifting the culture to a temperature at which the activation of leucine to an appropriate tRNA species became growth-rate-limiting led to a large increase in the high-affinity transport of leucine, isoleucine, and valine (system LIV-I) while the uptake of histidine and proline was unchanged. A similar increase was observed for branched-chain amino-acid binding protein activity. The temperature change did not alter the transport activity for any of these substrates or the level of the binding proteins in an isogenic strain with a normal leucyl-tRNA synthetase. The increase in transport activity observed in the mutant was prevented by inhibitors of protein and RNA synthesis and probably represents an increase in the differential rate of synthesis of the protein(s) required for transport. These experiments demonstrate that the repression of branched-chain amino-acid transport involves the interaction of leucine with its aminoacyl-tRNA synthetase and its cognate leucyl-tRNA species.